An Analysis of Speech Act in Ice Age Collision Course Movie Script - Achmad Fauzhi Abdullah; Arman Arman (ELITE: Journal of English Language and Literature, 2021)
This research is a pragmatic approach study of an analysis of illocutionary in ice age collision Course Movie Script. The objectives of this researcher are to find out the types of illocutionary acts are performed by all the characters' utterances, and to find out dominantly of types of illocutionary acts are used by all the character's utterances. The researcher used the content analysis qualitative method to describe and analyze the selected illocutionary acts which are watching movies and then classify them according to George Yule’s concept types of illocutionary acts. The researcher used content analysis which focuses on classifying the types of illocutionary acts and the dominantly of types of illocutionary acts in the ice age collision course movie carried out by all the characters. The researcher found that are the characters use all types of illocutionary acts. First representatives there are {Stating (3), Suggesting (1), Complaining (1)}. Second is directives, they are {Asking (3), Commanding (4), Forbidding (2), Demanding (2)}. Third, is commissions, they are {Promising (1)}, Forth is expressive, they are {Congratulating (2), Thanking (1) Welcoming (1), Apologizing (1)}, and the last is a declaration, they are {Declare (1), Naming (1)} Based on the data above, it reveals that all characters in their utterances dominantly used the illocutionary acts of Directive with the total of 11 data.